2015
DOI: 10.1093/jxb/erv245
|View full text |Cite
|
Sign up to set email alerts
|

SCF E3 ligase PP2-B11 plays a positive role in response to salt stress inArabidopsis

Abstract: HighlightAtPP2-B11, an F-box protein, enhances the salt stress tolerance by regulating AnnAt1 expression, repressing reactive oxygen species production, and disrupting Na+ homeostasis in Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 86 publications
(98 reference statements)
1
34
0
Order By: Relevance
“…Transcript levels for the VIP1 binding F‐box protein (AT1G56250) are upregulated by Agrobacterium tumefaciens and help to bring the transfer DNA inside the plant by degrading VirE2 and VIP1 proteins that coat the transfer DNA (Zaltsman et al, 2010). The expression of PP2‐B11 (AT1G80110) is elevated by salt stress, and overexpression lines of this gene are more tolerant to high‐salinity conditions (Jia et al, 2015). Lee et al (2014) showed that overexpression lines of PP2‐B11 are more sensitive to drought stress, suggesting that PP2‐B11 is a negative regulator in the response to drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…Transcript levels for the VIP1 binding F‐box protein (AT1G56250) are upregulated by Agrobacterium tumefaciens and help to bring the transfer DNA inside the plant by degrading VirE2 and VIP1 proteins that coat the transfer DNA (Zaltsman et al, 2010). The expression of PP2‐B11 (AT1G80110) is elevated by salt stress, and overexpression lines of this gene are more tolerant to high‐salinity conditions (Jia et al, 2015). Lee et al (2014) showed that overexpression lines of PP2‐B11 are more sensitive to drought stress, suggesting that PP2‐B11 is a negative regulator in the response to drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the distribution of Na + in plant roots, 1‐week‐old roots were subjected to water and 200 mmol/L NaCl treatments for 1 d, and the distribution of Na + was detected, according to previous reports (Jia et al 2015). The roots were also treated with water and 200 mmol/L NaCl for 7 d, and the Na + and K + ion contents were determined, as previously described (Shukla et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, we proved that AtPP2-B11 negatively regulates ABA-mediated processes by specifically targeting SnRK2.3 for degradation ( Fig 1 ; Fig 3 ; S10 Fig ; S11 Fig ), and the degradation of SnRK2.3 is induced by ABA in vitro and in vivo ( Fig 4 ). AtPP2-B11 encodes an F-box protein, and previous reports have shown that AtPP2-B11 is responsive to abiotic stress and is involved in plant tolerance to drought and salt stress [ 29 , 30 ]. In this study, we showed that AtPP2-B11 was expressed in multiple tissues and organs, and that it was induced by ABA ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , phloem protein 2-B11 (AtPP2-B11) is an F-box protein that acts as the substrate receptor for SCF type E3 ligases and which regulates LEA protein stability in drought-exposed plants [ 29 ]. AtPP2-B11 also affects the annexin1 protein level to positively regulate the response of plants to salt stress [ 30 ]. In this study, we show that AtPP2-B11 specifically targets SnRK2.3 for degradation.…”
Section: Introductionmentioning
confidence: 99%